Mitigate, adapt, prepare: a climate security agenda for the ASEAN defence ministers' meeting - Cook, Alistair David Blair (2023)
The Indo-Pacific is the region most prone to natural hazards and sea-level rise compounded by the effects of climate change. Viewed as a direct security concern for the impact caused by extreme weather events, climate change is also seen as a threat multiplier that worsens underlying political, social, and economic conditions, strains resources, and reduces military readiness. Coupled with the geopolitical realities of the region, the impact of climate change on regional security illustrates the need for defence and security cooperation. This can be achieved by establishing a comprehensive climate security framework that reflects the ASEAN Defence Ministers’ Meeting (ADMM) interests and ambitions regarding military contributions towards tackling the climate crisis and its impacts. It would further provide dialogue partners with entry points for engagement and an avenue to connect climate security initiatives across the Indo-Pacific region.